Revitalisasi Makam Tokoh Masyarakat KH. Hasyim Djamhari Dan KH. Abror Djamhari: Potensi Wisata Religi Dan Sejarah Dalam Meningkatkan Pariwisata Lokal Desa Danawarih - Mursekha, Mursekha; Wahyudin, Khoerul Ali; Pratiwi, Diana Lintang; Sari, Siti Armita; Maulida, Ashyfa Nur; Nabila, Hilwa; Futriana, Say; Fahmi, Muhamad Ulul; Baihaqi, Veron; Muqof, Alvin (Lembaga Penelitian, Penerbitan, dan Pengabdian Masyarakat, 2025)
The graves of public figures have magnetism and historical and religious value which can be an attraction in itself. This research uses a descriptive qualitative research method with data collection techniques through in-depth interviews with people who are selected to then become informants based on their competence in knowledge of objects in religious locations in Danawarih Village. KH. Hasyim Djamhari and KH. Abror Djamhari is an important figure in religious, social and organizational history, the graves of these two community figures certainly have high historical and spiritual value. Therefore, the potential for religious tourism destinations is certainly very potential, but this potential has not been fully exploited as an attraction for many people because not many people know these two figures except those who are involved in the organizational realm. This research aims to introduce these two figures through revitalizing the graves, inviting the public to revive their history and struggles and jointly protect and maintain the sites of these two figures. Revitalization of graves can be done by providing historical information. Through this research, it can be concluded that revitalizing the graves of community leaders can be an effective strategy in developing local tourism and can later attract tourists to make pilgrimages.